2015
DOI: 10.1007/s13277-015-3214-8
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine acyltransferase 1 (LPCAT1) upregulation in breast carcinoma contributes to tumor progression and predicts early tumor recurrence

Abstract: Breast cancer is the most common cancer in women worldwide. Aberrant lipid metabolism is an established hallmark of cancer cells. The recently isolated lysophosphatidylcholine acyltransferase 1 (LPCAT1), the most important enzyme in membrane biogenesis, has been currently implicated in cancer development and progression. The published literature lacks comprehensive reports on LPCAT1 expression in breast cancer and its impact on patients' outcome. We evaluated the immunohistochemical expression of LPCAT1 in 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 45 publications
4
51
0
Order By: Relevance
“…The results showed that LPCAT1 is up-regulated at both transcript and protein levels in ccRCC tissues, while the LPCAT2, LPCAT3 and LPCAT4 levels were comparable between the two groups. Similarly, higher LPCAT1 expression was reported in several other malignant tumours compared to normal tissues, including colorectal adenocarcinoma [12], prostate cancer [23, 27, 28], hepatocellular carcinoma [22], gastric cancer [29], breast cancer [30] and oral squamous cell carcinoma [31]. …”
Section: Discussionmentioning
confidence: 83%
“…The results showed that LPCAT1 is up-regulated at both transcript and protein levels in ccRCC tissues, while the LPCAT2, LPCAT3 and LPCAT4 levels were comparable between the two groups. Similarly, higher LPCAT1 expression was reported in several other malignant tumours compared to normal tissues, including colorectal adenocarcinoma [12], prostate cancer [23, 27, 28], hepatocellular carcinoma [22], gastric cancer [29], breast cancer [30] and oral squamous cell carcinoma [31]. …”
Section: Discussionmentioning
confidence: 83%
“…LysoPC is an abundant extracellular lipid that stimulates cell proliferation. Previous studies have shown that lysoPC is not only significantly altered in BC 28 but can also stimulate cancer cell migration and early tumor recurrence 23,29 . PS is an essential component of human cells and presents mainly on the inner leaflet of the cell membrane; however, the oxidative stress in BC cells can cause the exposure of PS.…”
Section: Discussionmentioning
confidence: 99%
“…PC can be synthesized by de novo and remodelling pathways [ 22 ]. In the remodelling pathway, LPCAT 1 is a key enzyme for the production of PC from lyso-phosphatidylcholine (LPC) by re-acylation, and its expression has been reported to increase in breast cancer with shorter survival rates [ 23 ]. Moreover, LPCAT1 is reported to be selective for LPC (16:1) and up-regulated LPCAT 1 increased PC (16:0/16:1) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%